KETIDAKSANTUNAN BERBAHASA ANAK USIA 11-12 TAHUN DI KELURAHAN TANGGIKIKI KECAMATAN SIPATANA KOTA GORONTALO DALAM BERINTERAKSI PADA GAME ONLINE FREE FIRE - Amalia Ziqra Doda; Dakia N. Djou; Rahmatan Idul (Jambura Journal of Linguistics and Literature, 2023)
Doda, Amalia Ziqra. Student ID 311417069, 2022 Language impolitiness of Grade V Student at SDN Elementary School Tanggikiki Village, Sipatana District, Gorontalo City, Interacting in Free Fire Online Game. Undergraduate Thesis, Studi Program of Indonesian Language and Literature, Faculty Letters and Culture Principal Supervisor: Dr. Dakia N. Djou, Hum; Co-supervisor: Rahmatan Idul, S.S M.A. Language is an imteraction tool humans trough speech or mevement. Language politeness is one of the languages part Politeness that plays a crucial role in facilitating interactions between individuals and groups. In addition, language politeness is improtant to take into account in communicating. The use of language in the form of speech has becoms casier due to technological advances in the modern era, particulalry many activities in daily life nowadays utilizing the electronic devuce, one of which is a cellphone that can download anything, including Free Fire online games. This study aimed to describe violations of politeness principles in the language in Grade V at SDN 89 Elementary School Tanggikiki Village Sipatana District Gorontalo City that occur in the process of interacting in Free Fire online games based on Leech politeness principles. It relied on a qualitative descriptive method. The data analysis technique used was data transcribing, while data collection techniques used interview technique, free-involved listening, note-talking, recordings, identifying, analizyng, and conclusioan drawing-findings: Impoliteness as a result of violating the maxim of wisdom found in student grade V, namely 9 violations, 7 violations of the maxim of generosity, 16 violations of the maxim of praise, 8 violations od the humility maxim, 6 violations of the maxim of agreement, and 7 violations of the maxim of sympathy. Keywords: Impoliteness, Language, Students.